Development of Human Digestion Puzzle Teaching Aids Based on Edutainment and Local Wisdom for Grade V at Special Needs Schools - Lismayanti, Anggi; Anjarini, Titi; Ngazizah, Nur (Jurnal Paedagogy, 2026)
This study aims to develop a learning medium in the form of a human digestive system puzzle that integrates edutainment principles and local wisdom values to improve learning outcomes in Natural Sciences (Ilmu Pengetahuan Alam / IPA) for students in a special school (SLB). The study employed a Research and Development (R&D) method using the ADDIE model, which consists of the stages of analysis, design, development, implementation, and evaluation. The research participants included five fifth-grade students and one teacher from SLB Muhammadiyah Purworejo. Data were collected through interviews, observations, expert validation, and learning outcome tests. Data analysis was conducted using descriptive quantitative and descriptive qualitative techniques. The validation results indicate that the developed learning media achieved a very high level of feasibility, with an average validity score of 87%. The practicality of the media reached 97.7% based on student responses and 80% based on teacher responses. Interview findings further reveal that the puzzle-based media helped students understand the structure and sequence of the digestive organs more concretely. Overall, the findings demonstrate that the edutainment- and local wisdom-based puzzle media are feasible, practical, and effective for enhancing science learning outcomes in special education settings.